Microwave plasma reactor with conical-reflector for diamond deposition. (July 2015) - An, K.; Yu, S.W.; Li, X.J.; Shen, Y.Y.; Zhou, B.; Zhang, G.J.; Liu, X.P.
Abstract: The modeling and design of a microwave plasma chemical vapor deposition (MPCVD) reactor with a conical-reflector cavity is presented. In the proposed reactor design, a mobilizable conical-reflector cavity, cylindrical reflector and mobilizable substrate were used to tune the system, which were different from the previous works. The electric field strength, plasma density, and tunability of the new MPCVD cavity were simulated using a finite element method (FEM). Simulations showed that this reactor possesses higher electron density than that of many other MPCVD reactors. When various frequencies microwaves were input, the tunability resulted in a minor reflection coefficient of 0.05. The good agreement of the plasma distribution between the simulation and experimental results validated the reliability of the simulation. Finally, diamond films have been successfully prepared using this new system. Experimental results indicated that the diamond films prepared using the new cavity were of high quality, at a deposition rate up to 12 μm/h. Highlights: A new type MPCVD reactor for diamond deposition was simulated and built. The reactor has a conical-reflector cavity for diamond deposition. The tunability of various microwave frequencies was a scarce report. The distance of cavity and outline of plasma validated the simulation reliably. Diamond films of high quality were prepared using the new reactor.